Experimental investigation of using ground source heat pump system for snow melting on pavements and bridge decks - Balbay, Asim; Esen, Mehmet (Academic Journals, 2010)
Melting snow with a hydronic heating system can eliminate the need for snow removal by chemical or mechanical means and provide greater safety for pedestrians and vehicles. So, a preliminary practical feasibility study of using a ground source heat pump (GSHP) system for snow melting on pavements and bridge decks had been performed for the first time in Turkey on the basis of a university study. The objective of this paper is to investigate the practicability of a GSHP system consisting of the vertical type single U-borehole heat exchangers with different lengths for snow melting on pavements and bridge decks. For this purpose, the vertical drilling of the borehole was performed for three different depths (30, 60, and 90 m) in Elazig, Turkey and U-tube heat exchangers were inserted into the corresponding boreholes. Experiments in winter season of 2006-2007 were carried out for melting snow on surfaces of the prototypes of bridge-slab (BS) and pavement-slab (PS) constructed for the experimental study. The effect of the depth of borehole coupled to heat exchanger on the snow melting system performance was experimentally investigated. This way, the snow accumulation on the surfaces of bridge-slab (BS) and pavement-slab (PS) were efficiently heated and thus melted. Development of the model is described in a companion paper.
Keywords: Snow/ice melting; ground source heat pump; bridge; pavement